2009
DOI: 10.1002/jmri.21674
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic hyperplasia: Evaluation of T1, T2, and microvascular characteristics with T1‐weighted dynamic contrast‐enhanced MRI

Abstract: Purpose: To evaluate microvascular and relaxation parameters of prostate and nearby muscle in patients with benign prostatic hyperplasia (BPH), and to examine measurement reproducibility. Materials and Methods:In this prospective study, 13 patients with BPH were imaged twice prior to surgery. The imaging protocol included a three-dimensional (3D) inversion-recovery turbo field-echo measurement of T 1 , a multiecho measurement of T 2 , and a high temporal resolution (1.5 seconds per volume) dynamic contrast-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 40 publications
3
42
2
Order By: Relevance
“…the repeatability of DCE MR imaging in prostate cancer, our results in terms of wCV are similar for K trans , with a higher wSD for v e ( 30,32,33 ). Contrary to other studies ( 23,28,31 ), we found that the repeatability of K trans in terms of wCV is the same as v e .…”
Section: Roi Analysis Parameterscontrasting
confidence: 58%
“…the repeatability of DCE MR imaging in prostate cancer, our results in terms of wCV are similar for K trans , with a higher wSD for v e ( 30,32,33 ). Contrary to other studies ( 23,28,31 ), we found that the repeatability of K trans in terms of wCV is the same as v e .…”
Section: Roi Analysis Parameterscontrasting
confidence: 58%
“…Estimates of all parameters apart from v e were unaffected, and so parameter estimates are shown for those datasets appropriate for a 2CXM (eight patients), with three of these lacking an estimate of v e . A potential solution to enable v e estimates in all patients is to increase the acquisition length to allow more time for contrast agent equilibration (47), but this must be set against ionizing radiation dose escalation for the CT studies.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The poor agreement of VFA with T1prep and inversion recovery measurements within an in vitro phantom may expose a flip-angle dependence of the SPGR slice profile (private commun., Dr. Hai-Ling Margaret Cheng), but formal evaluation is outside of the scope of this article. The most relevant contemporary comparison may be the application by Kershaw et al (24) of a 3D-inversion recovery turbo field echo technique for prostate evaluation at 1.5 T, achieving 2 Â 2 Â 5 mm interpolated voxels within a 4-minute scan time, although representative images were not provided.…”
Section: Comparative Performancementioning
confidence: 99%